Risk of gestational diabetes mellitus in women achieving singleton pregnancy spontaneously or after ART: a systematic review and meta-analysis. (22nd May 2020) - Bosdou, Julia K; Anagnostis, Panagiotis; Goulis, Dimitrios G; Lainas, Georgios T; Tarlatzis, Basil C; Grimbizis, Grigoris F; Kolibianakis, Efstratios M
Abstract: BACKGROUND: Women who achieve pregnancy by ART show an increased risk of obstetric and perinatal complications compared with those with spontaneous conception (SC). OBJECTIVE AND RATIONALE: The purpose of this systematic review and meta-analysis was to synthesize the best available evidence regarding the association between ART and gestational diabetes mellitus (GDM) in women with singleton pregnancies. The research question asked was whether the risk of GDM is higher in women achieving singleton pregnancy by ART compared with those achieving singleton pregnancy spontaneously. SEARCH METHODS: A literature search, in MEDLINE, Scopus and Cochrane databases, covering the period 1978–2019, was performed aiming to identify studies comparing the risk of GDM in singleton pregnancies after ART versus after SC. Both matched and unmatched studies were considered eligible. Meta-analysis of weighted data was performed using the random effects model. Results were reported as risk ratio (RR) with 95% CI. Heterogeneity was quantified with the I 2 index. OUTCOMES: The study reports on 63 760 women who achieved a singleton pregnancy after ART (GDM was present in 4776) and 1 870 734 women who achieved a singleton pregnancy spontaneously (GDM in 158 526). Women with singleton pregnancy achieved by ART showed a higher risk of GDM compared with those with singleton pregnancy achieved spontaneously (RR 1.53, 95% CI 1.39–1.69; I 2 78.6%, n  = 37, 1 893 599 women). The direction or the magnitude of the effect observed did not change in subgroup analysis based on whether the study was matched ( n  = 17) or unmatched ( n  = 20) (matched: RR 1.42, 95% CI 1.17–1.72; I 2 61.5%—unmatched: RR 1.58, 95% CI 1.40–1.78; I 2 84.1%) or whether it was prospective ( n  = 12) or retrospective ( n  = 25) (prospective studies: RR 1.52, 95% CI 1.27–1.83, I 2 62.2%—retrospective studies: RR 1.53, 95% CI 1.36–1.72, I 2 82.5%). Regarding the method of fertilization, a higher risk of GDM after ART versus SC was observed after IVF ( n  = 7), but not after ICSI ( n  = 6), (IVF: RR 1.95, 95% CI 1.56–2.44, I 2 43.1%—ICSI: RR 1.42, 95% CI 0.94–2.15, I 2 73.5%). Moreover, regarding the type of embryo transfer (ET), a higher risk of GDM after ART versus SC was observed after fresh ( n  = 14) but not after frozen ( n  = 3) ET (fresh ET: RR 1.38, 95% CI 1.03–1.85, I 2 75.4%—frozen ET: RR 0.46, 95% CI 0.10–2.19; I 2 73.1%). A higher risk of GDM was observed after ART regardless of whether the eligible studies included patients with polycystic ovary syndrome (RR 1.49, 95% CI 1.33–1.66, I 2 75.0%) or not (RR 4.12, 95% CI 2.63–6.45, I 2 0%), or whether this information was unclear (RR 1.46, 95% CI 1.22–1.75, I 2 77.7%). WIDER IMPLICATIONS: The present systematic review and meta-analysis, by analysing 1 893 599 women, showed a higher risk of GDM in women achieving singleton pregnancy by ART compared with those achieving singleton pregnancy spontaneously. This finding highlights the importance of early detection of GDM in women treated by ART that could lead to timely and effective interventions, prior to ART as well as during early pregnancy.